Shipwreck Evidence from Kilwa, Tanzania. (1st September 2016) - Pollard, Edward; Bates, Richard; B. ichumbaki, Elgidius; Bita, Caesar
Abstract : This article reports on the artefacts and environment of marine ballast and pottery sites identified through inter‐tidal and underwater survey around Kilwa, Tanzania, one of the most important medieval sultanates along the east African coast. An inter‐tidal site on the limestone fringing reef on the approaches to Kilwa Kisiwani Harbour and an underwater site within the harbour have been dated from associated pottery to c .8th–10th century and the 13th–16th century respectively. The presence of exotic basalt ballast is discussed as an indicator of wreck‐sites.